Sustainable development in the Caribbean : contemporary issues, challenges and opportunities (Organization of American States Washington, D.C., 2010)
Aggregates the diverse initiatives, including successes, challenges and opportunities of Caribbean SIDS, as it pertains to key aspects of sustainable development.
Keywords: SUSTAINABLE DEVELOPMENT